2-Arachidonoylglycerol: A signaling lipid with manifold actions in the brain. (July 2018) - Baggelaar, Marc P.; Maccarrone, Mauro; van der Stelt, Mario
Abstract: 2-Arachidonoylglycerol (2-AG) is a signaling lipid in the central nervous system that is a key regulator of neurotransmitter release. 2-AG is an endocannabinoid that activates the cannabinoid CB1 receptor. It is involved in a wide array of (patho)physiological functions, such as emotion, cognition, energy balance, pain sensation and neuroinflammation. In this review, we describe the biosynthetic and metabolic pathways of 2-AG and how chemical and genetic perturbation of these pathways has led to insight in the biological role of this signaling lipid. Finally, we discuss the potential therapeutic benefits of modulating 2-AG levels in the brain.